Accuracy of albumin creatinine ratio in comparison with albumine excretion rate for diagnosis diabetic nephropathy in type 2 diabetes mellitus - . Fatrinawati; . Windarwati; Osman Sianipar (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
Diabetic nephropathy (DN) is one of complications in diabetic patients manifested bymicroalbuminuria with minimal level of 30 mg/24 hour which is measured at least 2 timesin the period of 3 to 6 months. Microalbuminuria can be measured either albumin excretion rate (AER) or albumin creatinine ratio (ACR). Measurement of ACR is an alternative parameter recommended by WHO in 2011 to diagnose diabetic nephropathy since it is more convenient, fast and not requires special preparation. The purpose of this study was to investigate accuracy of ACR to diagnose DN in type 2 diabetes mellitus (T2DM) patients.This was a diagnostic test study involving 80 T2DM patients. In this study ACR value equal or more than 30 mg/g was independently and blindly compared with AER as the gold standard. The data were analyzed using 2x2 tables in order to calculate sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV). Other data were analyzed using statistic descriptive. Eighty T2DM patients consisting of 38males and 42 females participated in this study. They had suffered from T2DM on average9.5 years, and the average of ACR value was 55.5 mg/g. Total result of true positive andtrue negative was 77. Three result were false negative but none of false positive result.The ACR value equal or more than 30 mg/g had sensitivity, specificity, PPV, and NPV of95.9%, 100%, 100%, and 66.7% respectively. In conclusion, the ACR value equal or morethan 30 mg/g derived from morning urine sample can be used to diagnose DN in T2DMpatients.